High Temperature PDX of Precious/Base Metal Concentrates from Newmont's Phoenix Project, Using Controlled Precipitation of Sulphate Species to Enhance Silver Recovery - J. C. Gathje (Canadian Institute of Mining, Metallurgy and Petroleum, 2004)
Newmont acquired the Phoenix Project through the acquisition of Battle Mountain Gold in 2000. Shortly after the acquisition, Newmont Metallurgical Services (NMS) and Nevada Operations began development work on a process to Pressure Oxidize (PDX) precious metal rich copper concentrates from Phoenix using the Lone Tree PDX facilities at Valmy, Nevada. The high precious metals content of the Phoenix concentrate - Au up to -300 g/t and especially Ag, up to -1700 g/t - led Newmont to the development of a High Temperature PDX process that achieves high cyanide leach recovery of Au and Ag, from the PDX solids, without the requirement for a messy and expensive "lime boil" or sulphate destruction process. Base metals content in Phoenix concentrates range from: 15-25 % for Cu, 1-10 % for Zn and 0-2 % for Pb. Excellent solution extraction of Cu and Zn is achieved while Pb is precipitated in the PDX residue. In addition to achieving high Au and Ag recovery this process produces very clean PDX discharge liquors that require minimum effort to remove contaminant metals and PDX solids that have superior settling and filtration characteristics. All of these factors contribute to lower capital and operating costs for the overall process. This paper describes the laboratory and PDX pilot plant developments for this process.